ISOLATION OF SOME POTENTIAL PHYTOCOMPOUNDS FROM ADHATODA VASICA THROUGH GAS CHROMATOGRAPHY-MASS SPECTROSCOPY ANALYSIS - Khan, Aziz Mohammad; Bhadauria, Seema (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The aim of this study is to screen the medicinal compounds present in the leaves, shoots, and flowers of Adhatoda vasica by gas chromatography-mass spectroscopy (GC-MS) analysis. Methods: Plant leaves, shoots, and flowers were collected, washed, shade dried, and powdered. Methanol extracts of all plant parts were prepared by soxhlation method. All the plant part extracts were analyzed for the identification of phytocompounds present in plant parts using GC-MS and matched by the National Institute of Standards and Technology library. Results: A wide range of fatty acids and the heterocyclic compound was identified which is responsible for antibacterial, antifungal, anti-inflammatory, and antimycotic activity. Conclusion: The study concludes that A. vasica have many important important biologically compounds so it can be recommended as a plant of pharmaceutical importance.